2021
DOI: 10.3389/fgene.2021.629475
|View full text |Cite
|
Sign up to set email alerts
|

Luminal A Breast Cancer Co-expression Network: Structural and Functional Alterations

Abstract: Luminal A is the most common breast cancer molecular subtype in women worldwide. These tumors have characteristic yet heterogeneous alterations at the genomic and transcriptomic level. Gene co-expression networks (GCNs) have contributed to better characterize the cancerous phenotype. We have previously shown an imbalance in the proportion of intra-chromosomal (cis-) over inter-chromosomal (trans-) interactions when comparing cancer and healthy tissue GCNs. In particular, for breast cancer molecular subtypes (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 96 publications
4
24
0
Order By: Relevance
“…The effect of loss in long range co-expression is consistent with previous works of regulatory networks in breast cancer ( 10 , 12 14 , 33 , 53 ). The block-type structure of the basal subtype matrix suggests the utility of clustering analysis to compare the structural properties of the correlation matrices.…”
Section: Resultssupporting
confidence: 91%
“…The effect of loss in long range co-expression is consistent with previous works of regulatory networks in breast cancer ( 10 , 12 14 , 33 , 53 ). The block-type structure of the basal subtype matrix suggests the utility of clustering analysis to compare the structural properties of the correlation matrices.…”
Section: Resultssupporting
confidence: 91%
“…The aforementioned methods have different postulates and different approaches to detect communities. In that work (García-Cortés et al, 2021) it was demonstrated that, independent of the algorithm used to detect communities, the results were very similar in terms of the number of detected communities and the nature of the genes observed in each community.…”
Section: Application Example: Community Detection Methods For Cancer Networkmentioning
confidence: 91%
“…However, this is not always the case. For example, in García-Cortés et al ( 2021 ), for Luminal A breast cancer, an RNA-Seq-derived gene co-expression network was decomposed into communities by using four different methods: Fast greedy (Clauset et al, 2004 ), Infomap (Rosvall and Bergstrom, 2008 ), Leading eigenvector (Newman, 2006b ) and Louvain (Blondel et al, 2008 ).…”
Section: Application Example: Community Detection Methods For Cancer Networkmentioning
confidence: 99%
“…The apparently contradictory result suggested that the copy number alterations do not influence the structure of that community. On the other hand, a gene community formed by HLA family genes, presented a common pattern of amplification, but those genes were not differentially expressed (53). With the aforementioned in mind, we argue that CNVs are not as relevant as one could expect in terms of the gene clustering shown here.…”
Section: Discussionmentioning
confidence: 59%